Association of dietary intake of saturated fatty acids with obstructive sleep apnea: mediating effects of Life’s Crucial 9 - Gou, Ruoyu; Chen, Lili; Cheng, Zeyi; Cun, Jiawei; Li, Guanghua (Frontiers in Nutrition, 2025)
IntroductionObstructive sleep apnea (OSA) is a global public health issue. Life’s Crucial 9 (LC9) is recognized as a powerful tool for assessing cardiovascular health. Although the etiology of OSA remains unclear, saturated fatty acids (SFAs) and cardiovascular health are increasingly regarded as a non-negligible element. This study aims to assess the association between dietary intake of SFAs and the risk of OSA, and the mediating effect of LC9.MethodsBased on the National Health and Nutrition Examination Survey (NHANES), dietary questionnaires of participant were collected, and the average values of 24-h dietary recall data over 2 days were obtained. A continuous cross-sectional analysis with dietary energy adjustment was employed. Weighted multivariable logistic regression models were used to estimate the weighted odds ratios (ORs) and their 95% confidence intervals (CIs) for SFAs and OSA. Evaluate the mediating role of LC9 in the relationship between SFAs and OSA.ResultsA total of 13,563 participants aged 20 years and above were included in this study. The intakes of Sfa 4.0 and LC9 among participants with OSA were significantly lower than those in the normal population. After adjusting for confounding factors, total SFAs could increase the risk of OSA [Model 1, Q3, 0.03, 1.49 (1.03, 2.15); Model 2, Q3, 0.04, 1.47 (1.01, 2.13)]. It was emphasized that dietary intake of Sfa 12.0, Sfa 14.0, and Sfa 16.0 were protective factors for OSA, especially among participants aged 45–64 years and white individuals. Moreover, Sfa 12.0 exhibited a better protective effect in female participants [Q3, 0.04, 0.66 (0.45, 0.99)]. In addition, the cardiovascular health score - LC9 had a mediating effect in Sfa4.0 on OSA [Proportion of mediation: −0.035, 95% CI: (−0.058, −0.01); p= 0.002]. There was a nonlinear relationship between dietary intake of Sfa 12.0, Sfa 16.0, and Sfa 18.0 and OSA (P-Nonlinear = 0.013).DiscussionThese findings suggest that dietary mixtures of saturated fatty acids increase the risk of OSA. Among them, SFA 4:0 can increase the risk of OSA through the level of cardiovascular health. However, contrary to traditional beliefs, long-chain saturated fatty acids can reduce the risk of OSA.